Prevalence and pattern of non-communicable diseases among elderly in a sub-urban area of Delhi - Prabhakar, Tushar; Goel, Manish Kumar; Acharya, Anita Shankar; Rasania, Sanjeev Kumar (Indian Journal of Community Health, 2021)
Background: With increasing proportion of geriatric population across societies, the occurrence and prevalence of non-communicable diseases has been steadily increasing as well. The study tries to showcase the pattern and proportion of NCDs among the elderly population in a sub-urban part of Delhi. Aim & Objective: To assess the prevalence and study the morbidity profile of NCDs among geriatric population of Delhi. Materials & Methods: A community based cross sectional study was done in 350 elderly participants in Mehrauli, Delhi. Data was collected using a semi-structured questionnaire. Detailed general and systemic examination was also done. Results: A total of 87.4% of the study population was suffering from at least one NCD; 68% were having an already known NCD(s) while 19.4% were newly diagnosed during the study. 2.41 NCDs were found per patient. The prevalence of hypertension was 58%, 49.4% suffered from senile cataract, 32.9% had osteoarthritis, 30.3% had diabetes mellitus, and 26.9% had obesity. Hypertension and diabetes mellitus together were present in 18.3% while the combination of hypertension, diabetes mellitus and obesity was seen in 9.4% of the study participants. Conclusion: Burden of NCDs among the elderly was notably high with a large proportion of them having multimorbidity. It gets important to focus on preventive measures to delay the onset and stem the progression of NCDs to facilitate healthy ageing.